التطوير المهني لأعضاء هيئة التدريس بالجامعات: تجربة الجامعة الإسلامية العالمية بماليزيا - Ahmed Mohamed, Ismaiel Hassanein (2009)
Many who Academic staff in universities are teaching core competencies in the field of specialty. But they were not aware of modern teaching techniques during their university studies in the last three decades of the 20th Century: i.e.in the seventies, in the eighties and even in the nineties. Which they can dispense with their scientific and educational experiences. The current situation of education techniques updates trough Electronics devises will make it difficult to keep up with its developments without extensive, continuous and renewed educational technology training. In order to keep pace with this innovation of education, technological development must be in charge and teach scientifically and technically. They then be qualified to use all that is new or updated in their educational area to keep pace with the march of progress in the field of technical education. At the same time, to take advantage of the possibilities offered by their university or educational institution where they work, and improve on the teaching and learning in accordance with the levels and global talent in the field of education.